2018
DOI: 10.1038/s41433-018-0183-3
|View full text |Cite
|
Sign up to set email alerts
|

Mesopic and dark-adapted two-color fundus-controlled perimetry in patients with cuticular, reticular, and soft drusen

Abstract: In contrast to mesopic FCP, dark-adapted two-color FCP allowed for meaningful differential testing of rod and cone function in patients with drusen indicating predominant cone dysfunction in eyes with cuticular drusen and predominant rod dysfunction in eyes with reticular drusen. RPEDC thickness was the strongest predictor of the evaluated SD-OCT biomarkers for point-wise sensitivity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
50
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 46 publications
(56 citation statements)
references
References 53 publications
(86 reference statements)
5
50
1
Order By: Relevance
“…Binns et al 42 found the RIT at 128 eccentricity had a faster recovery than the 58 eccentricity in AMD group after exposed to 76% photobleach. A greater rod dysfunction at the paracentral macula has also been reported in the earlier studies by Flynn 13 and Pfau et al 43 When evaluating the RIT in our 30-minute testing protocol, we still found a large proportion of testing points in the RPD group that did not reach the rod intercept level after 30 minutes of dark adaptation. While slightly smaller than in our previous protocol where testing was only for 20 minutes (46%), 6 we still had about a third of all points in the RPD group not reaching the rod intercept level, and as such was uninformative to follow over time.…”
Section: Discussionsupporting
confidence: 87%
“…Binns et al 42 found the RIT at 128 eccentricity had a faster recovery than the 58 eccentricity in AMD group after exposed to 76% photobleach. A greater rod dysfunction at the paracentral macula has also been reported in the earlier studies by Flynn 13 and Pfau et al 43 When evaluating the RIT in our 30-minute testing protocol, we still found a large proportion of testing points in the RPD group that did not reach the rod intercept level after 30 minutes of dark adaptation. While slightly smaller than in our previous protocol where testing was only for 20 minutes (46%), 6 we still had about a third of all points in the RPD group not reaching the rod intercept level, and as such was uninformative to follow over time.…”
Section: Discussionsupporting
confidence: 87%
“…26,34,36,37 In this context highest impairment of rod function was found at 4°and 6°eccentricity of the fovea by Tan and coworkers, 34 whereas in another study highest abnormality of rod function in eyes with RPD was observed at 8°eccentricity after previous photobleach. 26 FCP testing recently showed a localized reduction of mesopic and especially scotopic retinal sensitivity corresponding to areas with RPD secondary to AMD, 25,27 which could be previously linked to a localized thinning of the partial outer retinal layer thickness. 18 In another work Wu and coworkers 38 did not observe a significant association of functional changes in mesopic FCP testing within presence of RPD in a cross-sectional study, whereas a reduced multifocal electroretinography (mfERG) implicit time, as well as reduced function, was exhibited in areas of RPD.…”
mentioning
confidence: 98%
“…22,23 Various studies found a functional impairment beyond best-corrected central visual acuity, using electroretinography (ERG) testing and fundus-controlled perimetry (FCP) (also termed as microperimetry). [24][25][26][27][28][29][30][31][32] A reduction of multifocal electroretinography (mfERG) function was seen in areas of RPD by Alten and coworkers. 23 In addition increased rodintercept time (RIT) in presence of RPD was observed by Flamendorf et al, 33 whereas within a longitudinal observational period of 12 months RIT was shown to remain stable in eyes with AMD and RPD.…”
mentioning
confidence: 99%
“…16 Higher background illumination is more desirable because it effectively saturates rod photoreceptors and produces cone-mediated sensitivity values. 34,52 The grid pattern is composed of testing points located at certain degrees from fixation, such as 10 , 16 , or 20 . 16,27,38 The retinal sensitivity at these points is then compared with the sensitivity of normal eyes.…”
Section: Microperimetry Testmentioning
confidence: 99%